The value of lipocalin-2 as an inflammatory marker in children with COVID-19 - V.V. Yevtushenko; I.Yu. Seriakova; S.O. Kramarov; N.S. Kyrytsia; V.O. Shadrin; O.O. Voronov (Zdorovʹe Rebenka, 2025)
Background. The purpose was to study the relationship between lipocalin-2 indicators and markers of inflammation and severity in children with COVID-19. Materials and methods. We conducted a cohort, observational, retrospective study involving 88 patients aged 1 month to 18 years with COVID-19 that was laboratory-confirmed by polymerase chain reaction. The children were hospitalized to the Kyiv City Children’s Clinical Infectious Disease Hospital (Kyiv, Ukraine). All participants were divided into two groups depending on respiratory manifestations: 46 children with lesions of the upper respiratory tract, who had manifestations of rhinitis, or sinusitis, pharyngitis, tonsillitis (control group) and 42 patients with lesions of the lower respiratory tract with clinical picture of laryngotracheitis, bronchitis or pneumonia (main group). During the comprehensive examination of the patients on the first day of their stay in the hospital, the blood serum was collected for further study of lipocalin-2 level by enzyme immunoassay. Human Neutrophil Gelatinase-associated Lipocalin, NGAL kit (BT LAB, China) with a working measurement range of 5–600 ng/ml and a sensitivity of 2.01 ng/ml was used. Statistical, analytical methods and method of empirical research were applied in the work. To calculate the obtained results, we used the statistical software EZR v. 1.54. Results. In patients of the control group, lipocalin level was 70.3 ± 27.7 ng/ml, while in the children of the main group, the indicator was higher, 124.60 ± 27.08 ng/ml (p = 0.03). According to the results of the study, a correlation was found between the level of lipocalin and the increased level of leukocytes (r = 0.889, p = 0.001), erythrocyte sedimentation rate (r = 0.53, p = 0.001), D-dimer (r = 0.393, p = 0.001), C-reactive protein (r = 0.54, p = 0.001) and X-ray changes in the lungs (r = 0.56, p = 0.001). Conclusions. There was a relationship between lipocalin-2 levels and markers of inflammation and severity of COVID-19 in children.